Implementation of Multi Channel-Single Phase in The Queue Information System of Julok Publik Health Center - Fazril Fazril; Raissa Amanda Putri; Aninda Muliani (Jurnal Penelitian Medan Agama, 2025)
Health services are closely related to queuing processes that directly affect service efficiency and patient comfort. At Julok Public Health Center, the queuing system is still conducted manually, resulting in long waiting times, overcrowding, and reduced service quality. This study aims to develop and implement a web-based queue information system using the Multi Channel–Single Phase model to improve the efficiency and quality of public health services. The research method applied is Research and Development (R&D) with a waterfall-based system development approach. The results indicate that the implemented system supports online registration, real-time queue monitoring, and queue data management, which contribute to reducing patient waiting time, improving service efficiency, and enhancing patient convenience. Therefore, the developed system provides a positive contribution to improving the quality of primary healthcare services.